PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2016 TENTANG PROSEDUR MEDIASI DI PENGADILAN PERSPEKTIF HUKUM ISLAM - Libriyanti, Oktavina (UIN Fatmawati Sukarno Bengkulu, 2017)
Mediation is a process of problem-solving negotiations, where impartial parties work with disputants to seek mutual consent. Mediation is also known in Islamic law that equates mediation with islah or Al-Sulh, is a process of dispute resolution in which the parties agree to end their case peacefully. The provisions of mediation in the last Court are regulated in supreme Court Regulation number 1 of 2016. Regulation Court are one of the courts under the Supreme Court in accordance with the mandate of constitution, therefore it is obligatory to enforce the provisions of mediation set forth in the Supreme Court Regulation. In accordance with its authority in terms of solving a particular dispute for Muslims, it means that the Religious Court, besides deriving from the positive law of Indonesia, must also derive from Islamic law. Likewise with the provisions on the implementation of mediation in the Court, in addition to following the Supreme Court, in addition to following the Supreme Court Regulation number 1 year 2016, also follow the provisions of mediation set forth in Islamic Law. Based on the above background this research reveal issues, what is the view of Islamic law in mediation procedures in religious court.